Development of Website-Based E-LKPD to Train Students' Historical Thinking on the Material of the Great World Revolutions Class XI State High School 1 Koto Kampar Hulu - Lili Rahma Yuni; Isjoni Isjoni; Asril Asril (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
SMAN 1 Koto Kampar Hulu is one of the high schools located in the Koto Kampar Hulu sub-district, Kampar Regency. At SMAN 1 Koto Kampar Hulu there is a shortage of learning media, which makes the learning process boring, especially in history subjects. Teachers still use conventional methods and do not use media, so learning is less effective. The research was conducted with the aim of developing the enthusiasm of students at SMAN 1 Koto Kampar Hulu towards history subjects by developing website-based E-LKPD media and conducting E-LKPD feasibility tests for history learning at SMAN 1 Koto Kampar Hulu, and looking at students' responses regarding website-based E-LKPD media. The research method used is 4D. Based on research conducted by E-LKPD learning media (electronic student worksheets) it was declared suitable for use in the teaching and learning process after being analyzed by material experts, questions, media, and students. The results of the website-based E-LKPD validation on the material of world's great revolutions by material experts get an average result score of 4.7 with a very feasible category, question experts with an average score of 4.6 with a feasible category, media experts with a score an average of 4.2 with a very feasible category, and the results of student respondents in the small group test with an average score of 4.79 with a very feasible category. The results of student respondents in the large group test with an average score of 4.86 with a very decent category. In this study there are still research limitations, where the research produced is still at the beginner level, so the researchers hope that there will be research that can develop this E-LKPD learning media so that it can be applied to other schools.